1981
DOI: 10.1002/jat.2550010109
|View full text |Cite
|
Sign up to set email alerts
|

Chemical carcinogensis in vitro: An improved method for chemical transformation in Rauscher leukemia virus‐infected rat embryo cells

Abstract: In vitro assay for carcinogenesis, using mammalian cells, provide opportunity for rapid and inexpensive means, compared to in vivo assays, for studying carcinogenesis and for identifying potential carcinogens. These assays must, however, be shown to be reproducible, reliable and able to detect a variety of known carcinogens before they can be recommended for general use. We have, independently, reproduced a transformation assay which utilizes murine leukemia virus-infected rat embryo cells as targets. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The predictive value of the survival in aggregation assay for the detection of carcinogens is consistent with previously published reports for the RLV-infected Fischer rat embryo cell focal assay [Freeman et al, 1973b;Traul et al, 1981a;Dunkel et al, 1981;Heidelberger et al, 19831. A major advantage over earlier systems, however, is the rapidity with which the results are obtained.…”
Section: Suketalsupporting
confidence: 89%
“…The predictive value of the survival in aggregation assay for the detection of carcinogens is consistent with previously published reports for the RLV-infected Fischer rat embryo cell focal assay [Freeman et al, 1973b;Traul et al, 1981a;Dunkel et al, 1981;Heidelberger et al, 19831. A major advantage over earlier systems, however, is the rapidity with which the results are obtained.…”
Section: Suketalsupporting
confidence: 89%
“…The Panel noted a series of studies which had investigated potential modulating effects of various fatty acids (lauric acid, oleic acid, myristic acid, capric acid, caprylic acid, stearic acid and palmitic acid) administration on the development of cancer in animal models treated with an initiating agent (Dayton et al, 1977;Jain et al, 1980;Traul et al, 1981;Hogan and Shamsuddin, 1984;Sakaguchi et al, 1984;Cohen et al, 1986;Habib et al, 1987;Lasekan et al, 1990;Hubbard and Erickson, 1991;Numata et al, 1994;Zusman et al, 1997;Kimura, 2002). With the exception of linoleic at high doses, most of these studies have reported protective effects of free fatty acids.…”
Section: Initiation-promotion Studiesmentioning
confidence: 99%